Faculty perception of online education: considerations for the post-pandemic world - Ahmed, Vian; Anane, Chiraz; Alzaatreh, Ayman; Saboor, Sara (Frontiers in Education, 2023)
In the post-COVID era, academic institutions adapted curricula, utilizing aspects of the online delivery in full or partially. Consequently, this research focuses on identifying the factors that influence faculty perceptions of effective online delivery in higher education and comparing them with students' perceptions. The study involves semi-structured interviews with 15 faculty members at a renowned university to gain insights into their online teaching experiences during the pandemic.Additionally, 51 faculty members participated in a survey using the Relative Importance Index (RII) method to determine the most significant practices impacting online delivery. The results indicate that the most concerning factor for faculty during online delivery is facilitating students' engagement and interactions in class, with an RII of 0.94. Controlling academic dishonesty during assessments receives a relatively lower concern with an RII of 0.67. Making lectures interactive is identified as the most challenging practice for faculty. Comparing the findings with students' perceptions based on previous studies, both groups emphasize the significance of effective communication, interaction, and the use of technology. Faculty prioritize the delivery and organization of lectures, while students focus on engagement and interactive elements. Faculty value organization and relevance in assignments, while students emphasize instructor qualities and responsiveness.